Multi-resistant Candida Species: A Global Public Health Problem: A Systematic Review - Lima Vital, Eliza; Carnovale, Susana Irma (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Candida yeast infections are frequent in the hospital population. These fungi are part of the normal microbiota of the skin and mucous membranes of humans. Although almost 150 species are recognized in the genus, 90% of invasive processes are caused by Candida albicans, Candida glabrata, Candida tropicalis and Candida parapsilosis. Candida albicans continues to be the predominant species, although the frequency of non-albicans Candida (CNA) is increasing. These include the latter species with intrinsic resistance to fluconazole such as C.krusei (now known as Pichia kudriavzevii) or decreased resistance to fluconazole such as C glabrata and decreased resistance to echinocandins such as C parapsilosis. Candida auris has been reported as the causative agent of invasive infections in humans in at least 47 countries. It is transmitted through contact with contaminated environments or with colonized people. In November 2022, two cases of infection by this fungus were detected for the first time in Argentina. Material and methods: In this systematic review, 427 articles searched on platforms such as Pubmed, Google Scholar, and Epistemonikos were found, and 10 were used to carry them out. Results: The articles chosen study hospitalized patients in intensive care units who present candidemia due to multiresistant fungi. The results show us that therapeutic success is associated with the correct identification of fungi and antifungal susceptibilities tests. The vast majority of isolated cases showed resistance to at least one of the three main classes of antifungals. Conclusion: Nosocomial outbreaks due to multiresistant fungi present a high mortality rate associated with therapeutic failure due to the difficulty in identifying some fungi with routine techniques. It was also discovered that the comorbidities of each patient is a risk factor for infection. Finally, it was shown that the protocols for decontamination and cleaning of the patient and their environment, together with the isolation of positive patients, are effective in stopping horizontal transmission between patients